THE EFFECT OF REWARD ON LEARNING MOTIVATION OF ELEVENTH-GRADE STUDENTS AT SMA NEGERI MUMBULSARI IN HISTORY SUBJECT: Pengaruh Pemberian Reward terhadap Motivasi Belajar Siswa Kelas XI SMA Negeri Mumbulsari pada Mata Pelajaran Sejarah - Roihatus Fafaisa; M. iqbal Ibrahim Hamdani; Adzkiyak Adzkiyak (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effect of reward implementation on students’ learning motivation in History among eleventh-grade students at SMA Negeri Mumbulsari. A quantitative approach was employed using a simple linear regression method. The sample consisted of 71 students selected through random sampling. Data were collected using validated questionnaires and supporting documentation. The results showed that the use of reward strategies—such as verbal praise, additional points, and simple gifts—had a significant positive effect on students’ learning motivation. The regression equation obtained was Y = 12.174 + 0.635X, with a t-value of 9.106 (greater than the t-table value of 1.667) and a significance level of 0.000 (< 0.05). The coefficient of determination (R²) was 0.546, indicating that 54.6% of students’ learning motivation was influenced by the reward variable, while the remaining 45.4% was attributed to other factors.